Título Padrão - Sousa Martins, Thais; Darley Figueiredo da Silva, Raimundo; Barbosa Veneza, Ivana; da Conceição Praxedes Santana, Paula; Ramos Correa, Rafael; Caroliny Negrão Santa Brígida, Nicolly; da Silva Gonçalves, Jakson; de Cássia Martins da Silva, Rita; Carvalho de Mesquita, David; Antônio de Freitas Lutz, Ítalo; Fernanda Evangelista Gomes, Grazielle (Arquivos de Ciências do Mar, 2021)
Bragança is an important municipality in Brazil regarding fishery production. In spite of its important for regional economy, data related to local fisheries such as the production and consumption profiles of commercial species are scarce. Therefore, the goal of this study was to provide an inventory of commercialized fishes in the street market of Bragança along with commercialization parameters. The data collection comprised information based on a questionnaire directed to fishmongers in two sites of the street market (“mercado” or indoor market and “feirinha” or outdoor market) for a 17-month period. The analyzed data included the abundance, seasonality and price of the commercialized species. A total of 103 commercial names were reported, representing about 98 species from 40 families and 15 orders. The indoor and outdoor market differed in relation to consumer’s profile and to the structure, volume, variety, quality and prices of commercial species. The volume and the diversity of commercial species in the indoor market were inferior to those observed in the outdoor market. The most abundant species in the outdoor market were influenced by dry and rainy seasons. This work represents the most reliable analysis in the street market of Bragança, being relevant to the management of regional fisheries. Keywords: Bragança, M. ancylodon, fishing dynamics, fish.